PERANCANGAN PUSAT PERAWATAN ANJING DI KOTA PONTIANAK - Yulia, Siska; Zain, Zairin; Kalsum, Emilya (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Human needs are becoming increasingly different as time progresses. Types of human needs can be tertiary needs, such as the hobby of having a pets. The hobby to have a pets can be amongs popular animals like dogs or cats. It is not rarely for Pontianak people to pets a dogs. Dogs are social animals that can be a friends for humans and they can entertain people when they are feels stressed and with this interaction, we can increase and strengthen our bond with these animals. In Pontianak City, we can still find several facilities such as pet shops, pet grooming, pet hotels and pet clinics, but these facilities are located far apart and there is still no way to get these facilities in one location in Pontianak City. From these problems, the question arises about how to create facilities that can accommodate these facilities in one place. Therefore, the design of the Dog Care Center in Pontianak City was provided with the aim of providing facilities that focus on needs for dogs and providing proper care. The presence of this Dog Care Center in Pontianak is designed and expected to provide complete and appropriate facilities and have a positive impact on dog owners and can also maintain the balance of the surrounding environment.